A transição para o Ensino Fundamental II: desafios da coordenação pedagógica e da docência - Cozer, Tatiana Tais (2020)
The present dissertation entitled “A Transição para o Ensino Fundamental II: Desafios da Coordenação Pedagógica e da Docência” focused on reflecting on the transition process from the initial years to the final years of elementary education. The main objective of the study was to investigate the processes that take place at the moment of the transition from the 5th to the 6th year of elementary education and how the continuing education of teachers proposed by the pedagogical coordination contributes to the understanding of this movement. The research is characterized by the qualitative bias, classified as action research, with a descriptive-interpretative focus and with theoretical support in a bibliographic study, considering the contributions of authors such as: Barreto (2011, 2015), Domingues (2015), Freitas (2014), Fusari (1992), Gatti (1996, 2016), Libâneo (2001), Nóvoa (1992, 1999, 2000, 2003), among others. The research was developed with 5th, 6th and 7th year students and teachers from EEEM Professora Helvética Rotta Magnabosco. The generation of data for the study took place through conversation circles with the respective classes and with teachers through the class council and continuing formation with the collective of teachers. Regarding the transition from the 5th to the 6th year of elementary school, it was possible to observe, from the students' point of view, seven categories that represent the main processes that occur during the transition: migration to pluridocence, teaching and learning process, family orientation, indiscipline, school performance, class shift and teaching profile. From the perspective of the teachers, five categories were evidenced that registered the weaknesses related to the dynamics of the teaching and learning process of students in a transition situation: immaturity, dependence and lack of limits, professional profile, multidisciplinary, affectivity and class advice. During the process of observation and listening of those involved in the research, it became possible to build mediation possibilities, both for students and for teachers, pedagogical coordination and parents. Such possibilities resulted in the final product of this dissertation, which will be delivered to the EEEM. Professora Helvética Rotta Magnabosco and for the 15th Regional Education Coordination.